Biogenic copper nanoparticles as a novel biocontrol strategy for Ascochyta blight in chickpeas - Vasquez-Espejo, Carina (2026)
Ascochyta blight (caused by Ascochyta rabiei infection) is a devastating disease in chickpea crops. Farmers apply fungicides several times once symptoms appear, with poor control efficacy. Chemical fungicides, despite their widespread use, have harmful effects and an environmental impact. The lack of control strategies, plus the impact of excessive fungicide use, underscores the need to explore novel and sustainable biocontrol alternatives. Furthermore, the stability and bioavailability of fungicides could be improved by a formulation as nanoparticles (NPs), by chemical or biological synthesis. While the chemical synthesis requires harmful chemicals and high costs, the biological synthesis uses biological components as reducing and stabilizing agents. Then, the biological synthesis minimizes harmful chemicals and adverse effects on humans, animals, and the environment, in alignment with the “One Health” approach. The nanoscale size is key, as it increases the surface area for contact with the target, thus enhancing the efficacy. The objective of this study was to evaluate the antifungal activity of biosynthesized copper nanoparticles (CuNPs) against A. rabiei. The biosynthesized CuNPs (CuNPs2 and CuNPs3) exhibited significantly greater inhibition compared to copper sulfate salt. They showed in vitro inhibition as much as twice that of the copper salt. CuNPs2 and CuNPs3 successfully reduced the disease incidence in chickpea leaves by > 60 % demonstrating their potential as an alternative biocontrol strategy. The superior efficacy of CuNPs was attributed to their nanoscale properties and biogenic synthesis method. The use of bioderived CuNPs represents a promising and cost-effective alternative to traditional fungicides, advocating for more sustainable agricultural practices.